1999
DOI: 10.1080/713803557
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoserine Aminotransferase, the Second Step‐Catalyzing Enzyme for Serine Biosynthesis

Abstract: As a step toward analyzing the serine biosynthetic pathway in mammals, we have studied the properties of phosphoserine aminotransferase, the second step-catalyzing enzyme. The K(m) values for 3-phosphohydroxypyruvate and L-phosphoserine are 5 and 35 microM, respectively, and those for glutamate and alpha-ketoglutarate are 1.2 and 0.8 mM, respectively. The product inhibition studies strengthened the support for a ping-pong mechanism and allowed evaluation of Ki values for the four substrates. The equilibrium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Our result showed that a temperature of 25°C was suitable for expression of bmPSAT activity. Under the optimum condition, we found that the K m (6.0 mM) for PHP showed lower affinity than that of B. circulans (0.1 mM at pH 7.0; Kapetaniou, Thanassoulas, Dubnovitsky, Nounesis, & Papageorgiou, ) The K m value of bmPSAT toward glutamate (1.9 mM) was similar to that from bovine serum (1.2 mM), sheep brain (0.7 mM), E. histolytica (0.78 mM), and B. circulans (1.0 mM; Ali & Nozaki, ; Baek et al, ; Basurko, Marche, Darriet, & Cassaigne, ; Hirsch & Greenberg, ) but was lower than that from A. thaliana (5.05 mM; Ali & Nozaki, ). These results suggested that bmPSAT may be able to recognize PHP and glutamate as substrates and NADPH as a cofactor.…”
Section: Discussionmentioning
confidence: 73%
“…Our result showed that a temperature of 25°C was suitable for expression of bmPSAT activity. Under the optimum condition, we found that the K m (6.0 mM) for PHP showed lower affinity than that of B. circulans (0.1 mM at pH 7.0; Kapetaniou, Thanassoulas, Dubnovitsky, Nounesis, & Papageorgiou, ) The K m value of bmPSAT toward glutamate (1.9 mM) was similar to that from bovine serum (1.2 mM), sheep brain (0.7 mM), E. histolytica (0.78 mM), and B. circulans (1.0 mM; Ali & Nozaki, ; Baek et al, ; Basurko, Marche, Darriet, & Cassaigne, ; Hirsch & Greenberg, ) but was lower than that from A. thaliana (5.05 mM; Ali & Nozaki, ). These results suggested that bmPSAT may be able to recognize PHP and glutamate as substrates and NADPH as a cofactor.…”
Section: Discussionmentioning
confidence: 73%
“…4b). We observed the steepest slope for the SNP in the amino acid biosynthesis gene PSAT1 (2.7 ΔP/km; [73]), which was over three times steeper than the slope for any other SNP. Steep slopes represent a rapid change in allele frequency and suggest relatively strong selection.…”
Section: Resultsmentioning
confidence: 99%
“…The organic layer was evaporated and purified by silica gel chromatography (Cyclohexane/EtOAc: 8/2) to give the title compound as a white solid (0.59 mmol, 0.13 g, 52%). 1-Morpholino-2-phenylethan-1-one (28). To a solution of 2-phenylacetic-acid (0.50 g, 3.70 mmol, 1 equiv.)…”
Section: Synthesis Of Compounds 22-39mentioning
confidence: 99%